Pelatihan Teknik Sampling Dan Survey Untuk Meningkatkan Kinerja Karyawan PT Mustika Jaya Lestari Semarang - Yulianto, Safaat; Khikmah, Laelatul; Ambarwati, Atika Nurani; Wijayaningrum, Taswati Nova; Sulistijanti, Wellie (Intimas, 2024)
Survey is a very important step in supporting decision making in various fields. In conducting surveys, surveyors are required to collect data that must be approached by statistical methods. To be able to understand and conduct surveys correctly, an understanding of statistical analysis is needed, especially on quantitative data. The low understanding and analysis of data and the use of statistical methods make survey results with quantitative data cannot be completed correctly. To be able to conduct surveys correctly, surveyors are also required to understand sampling techniques and statistical analysis in accordance with statistical rules. Community service in the form of training on Sampling and Survey Techniques can provide the benefits of understanding statistics and skills in using statistical methods and software to support quantitative surveys, especially in the field of animal husbandry. In addition, community service in the form of training can also provide significant benefits for employees of PT Mustika Jaya Semarang in conducting surveys of farmers and analyzing the resulting survey results.